IMPLEMENTATION OF THE HIWALAH ACADEMIC IN SOCIAL ENVIRONMENT AND SHARIA FINANCIAL INSTITUTIONS - Nur Vianti (RADJA PUBLIKA, 2023)
Debt has become commonplace to meet the needs of human life. However, because it is a loan, it must be returned, and sometimes not everyone can return it at the agreed time. Therefore, Islam offers a solution in the form of the Hiwalah Contract. Hiwalah is the transfer of debt from the person who owes it to someone else who is able to pay it. Hiwalah is a unique system suitable for adaptation by humans, because Hiwalah is part of human life in muamalah. The legal basis for implementing Hiwalah is the Qur'an, Hadith, Ijma' and Qiyas. Hiwalah is not used to solve account payments problems but more than that it also serves as a transfer of funds from one person to another or from one group to another. In this case, the banking system has also practiced the Hiwalah contract. The debt transfer system is a transfer of debt burden from the person who is in debt to the person who is obliged to pay because there are similar debt levels. To transfer debt, you can use collateral which is joint property in the financing, so it can be transferred to those who are able to bear it with the guarantee that the assets are transferred to the guarantor. Even on the other hand it could also be for other people who want to continue the stalled financing with the assets being financed as collateral then there is a transfer of use to the insurer. The debt transfer system is a transfer of debt burden from the person who is in debt to the person who is obliged to pay because there are similar debt levels. To transfer debt, you can use collateral which is joint property in the financing, so it can be transferred to those who are able to bear it with the guarantee that the assets are transferred to the guarantor. Even on the other hand it could also be for other people who want to continue the stalled financing with the assets being financed as collateral then there is a transfer of use to the insurer.